Msmes Performance Of Indonesian Textile Reviewed From Social Capital, Psychological Capital And Entrepreneurial Orientation - Sonaji Sonaji; Tri Siwi Agustina (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to investigate the influence of social capital and psychological capital on the business performance of wastra nusantara’s MSMEs with the mediation of entrepreneurial orientation. The object of this research is Wastra Nusantara MSMEs from 6 cities/district in East Java with a total of 55 business owner. This type of research is quantitative while the data collection method uses a questionnaire that has been tested for validity and reliability first. To prove the hypothesis, the statistical test tool Smart - Partial Least Square (PLS) version 3.2.9 is used. The results of the study recommend that entrepreneurial orientation is able to partially mediate the effect of social capital on the performance of the wastra nusantara’s MSMEs, as well as entrepreneurial orientation is able to partially mediate the effect of psychological capital on the performance of the wastra nusantara’s MSMEs. The managerial implications of this research are aimed at MSME coaches, namely Bank Indonesia and the wastra nusantara’s to better understand and help them survive and thrive in the midst of an increasingly challenging business environment.